Total Synthesis of (+)-Cladospolide A - Prasad, Kavirayani R.; Revu, Omkar (Synthesis, 2012)
A stereoselective total synthesis of (+)-cladospolide A from d-ribose is described. Key features of the synthesis include olefin cross metathesis and Yamaguchi lactonization.
Keywords: cladospolide A; natural products; total synthesis; macrolactone